Pañcasikkhāpada: Moral Practice for Family in Buddhism - Pongpha, Kanda; Wuthidhammo, Pharamaha Chitnaretes (Journal of International Buddhist Studies, 2016)
The aims of the article are to explain Pañcasikkhāpada as the moral practice for family and to apply them in daily life to obtain the peace and happiness. It starts with the concept of Pañcasikkhāpada as the moral practice for family according to Buddhism and The essential practice of the fve precepts for the members of family. Next, it is discussed the ways to apply in daily life by using the activities that concerned with human beings’ life. The benefts of practice the precepts are peace and happiness of the members of family and passing on to society.